Christa Kühnhold: Der Begriff des Sprunges und der Weg des Sprachdenkens - Toftdahl, Hellmut (Grundtvig-studier, 1976)
Der Begriff des Sprunges und der W eg des Sprachdenkens (lit. ‘ The Concept of the Spring And the Method of Linguistic Thought’) by Christa Kühnhold, Berlin - New York 1975 Reviewed by Hellmut Toftdahl The reviewer recommends this doctorate on Kierkegaard to all those interested in Grundtvig, partly on account of its method, partly because it presents the side of Kierkegaard that is in agreement with Grundtvig, namely, the clash with abstract speculation. Christa Kühnhold shows that where dialectics end, Kierkegaard draws on the resources latent in the nuances of the Danish language. Her understanding of Kierkegaard’s vocabulary reminds one of Grundtvig’s experience with language. She has collected material on such concepts as: reality, truth, suffering, Spring, beginning, conversion, and guilt. Her semantic approaches are supplemented by her knowledge of linguistic history and mythology.